Analisis Dampak Media Sosial dalam Komunikasi Interpersonal: Kajian Literatur Deskriptif 2019–2024 - Rima Sasfira; Hagi Julio Salas (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This article analyzes the impact of social media on interpersonal communication by identifying both its positive and negative effects. Social media facilitates individuals to stay connected and communicate despite distance and time, and it also expands social networks that can strengthen interpersonal relationships. However, behind this convenience, social media also poses challenges in maintaining the quality of face-to-face interactions and emotional closeness. Excessive use of social media may reduce direct interactions, which are essential for building deep social bonds. The phenomenon of phubbing—where attention is more focused on digital devices than on people nearby—illustrates the negative impact of social media on social relationships. Additionally, dependence on social media can increase feelings of loneliness, anxiety, and social isolation, which weaken the quality of interpersonal relationships. This study shows that while social media offers convenience and benefits in expanding social connections, unwise usage can lower the quality of interpersonal communication. Therefore, it is important to use social media wisely, maintain a balance between the digital and real world, and enhance digital literacy to support healthy and meaningful social relationships